THREE-ACT STRUCTURAL APPROACH IN THE JAM KOSONG: FILM SCRIPT SATIRE COMEDY - Warni, Desi; Abidin, Zainal; Asril, Asril (ISI Press Institut Seni Indonesia Surakarta, 2026)
The three-act structure is dominant in film screenwriting, including the satirical comedy genre, as seen in Jam Kosong (Empty Hours). However, these studies tend to focus on drama, with little attention paid to satirical comedy. The choice of satirical comedy as a creative form is based on both aesthetic and conceptual considerations. Satire has a distinctive character as a medium for social criticism that operates through irony, hyperbole, and paradox. The combination of satirical comedy with a three-act structure provides significant dramatic advantages. Therefore, this article seeks to enrich academic discourse on film screenwriting and the application of narrative structure in the satirical comedy genre. This study adopts an artistic research design, which positions artistic practice as a form of creative and critical inquiry integrated with educational objectives. This study reveals the most important finding: the three-act structure in the Jam Kosong screenplay is effective in constructing a satirical comedy narrative that critiques social issues such as educational inefficiency and bureaucratization, while still entertaining audiences through ironic humor.